Persepsi tentang Kesehatan Diri dan Faktor-Faktor yang Mempengaruhi Perilaku Berobat Ke Dukun Cilik Ponari - Putriyani, Putriyani (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
Abstract Health is an important factor that is needed to carry out daily activities. Various methods are used to obtain health, such as the use of modern medicine and traditional medicine. In early 2009, the media in Indonesia, many carried stories about a little boy named Muhammad Ponari believed to cure various diseases by dipping a stone into the water. Information is rapidly spreading in the community, so there are hundreds of people who queued to get treatment every day. Basically, the government has developed a policy that all levels of society to seek treatment at the medical places, such as hospitals, health centers, clinics, and others.The purpose of this study was to determine the perception of their own health and the factors that influence the behavior of the little shaman went to Ponari. This study used the phenomenological approach because it can reveal the meaning darisebuah experience, in addition to the data analysis approach used was content analysis.Based on the results of the research through interviews and observation, informants had positive perceptions about their own health, even though the illness is classified as a severe illness. Health itself is determined by how much work is done to avoid the disease, in other words the self alone plays an important role for the creation of the expected health (internal locus of contol). There are 4 factors that influence the behavior of the little shaman went to Ponari, those factors is the perception of the severity of the disease, the benefits of medication in the little shaman Ponari, many obstacles modern medical treatment, and the belief in a supernatural power. Keywords: Perception, Behavioral Treatment, Shaman Little Ponari